Electrospun cellulose nanocrystals/poly(methyl methacrylate) composite nanofibers: Morphology, thermal and mechanical properties. (15th February 2019) - Ni, Xiaohui; Cheng, Wanli; Huan, Siqi; Wang, Dong; Han, Guangping
Highlights: Thermal stability analysis indicates the effect of hydrogen bonding of CNC-PMMA on Tg . Adding CNCs can improve the mechanical properties of CNC/PMMA fibers. The CNCs obviously affect the surface morphology of the composite fibers at high RH. Abstract: An electrospinning process was utilized to fabricate composite nanofibers of poly(methyl methacrylate) (PMMA) reinforced with cellulose nanocrystals (CNCs). The effect of environmental relative humidity on the microstructure of CNC/PMMA nanofibers was investigated. Results showed that fiber surfaces of CNC/PMMA appeared smooth. Fibers had gradually decreasing diameters and lower diameter variations as CNC loading increased. The thermal property of CNC/PMMA nanofibers was also enhanced due to hydrogen bonding between PMMA molecular chains and CNC nanoparticles. Compared to pure PMMA fibers, the storage modulus and tensile strength of composite nanofibers were pronouncedly improved. By increasing relative humidity of the electrospinning environment, these nanofibers showed prominent nanoporous surfaces while the surface roughness and porosity of CNC/PMMA nanofibers increased. Furthermore, CNCs were critical to accelerating the evolution of pores and increasing surface roughness. Our findings can provide useful guidelines for the fabrication of nanofibers with desired properties and pore structure by electrospinning.